Research on the Current Situation and Causes of Food Additives Problem in China - Li Zimu (SHS Web of Conferences)
In recent years, the food additives problem in China remains serious although it has been alleviated, which inevitably triggers public concern. In this study, 216 citizens’ knowledge of food additives was investigated using a combination of literature research method and questionnaire survey to systematically research the current situation, causes and impacts of the food additives problem in China. The results indicate that China’s current food additive standards to a large extent take the GRAS (Generally Recognized As Safe) of the United States for reference. However, the results of sampling tests still reveal severe food additives problems, especially the common problem of illegal additives by enterprises. Besides, the public’s knowledge of food additives is limited. Thus, their concerns focus on color and taste additives, whereas their acceptance of functional additives is higher. The industry uses additives mainly to save costs and improve the taste. However, weak regulation is a key factor leading to the problems. Moreover, the public believes that food additives have both advantages and disadvantages, with the advantages being improved taste and quality, and the disadvantages being possible psychological dependence and health hazards. Most people believe that the disadvantages outweigh the advantages. Finally, considering the major problems of food additives in China, the public’s general concern and the causes of the problems, this paper puts forward suggestions for solving the problems of food additives in China.